2014
DOI: 10.1074/jbc.m114.557025
|View full text |Cite
|
Sign up to set email alerts
|

Type 1 Cannabinoid Receptor Ligands Display Functional Selectivity in a Cell Culture Model of Striatal Medium Spiny Projection Neurons

Abstract: Background:To understand the differential response to cannabinoids, we examined the functional selectivity of type 1 cannabinoid receptor (CB 1 ) agonists in a cell model of striatal neurons. Results: 2-Arachidonylglycerol, ⌬ 9 -tetrahydrocannabinol, and CP55,940 were arrestin2-selective; endocannabinoids and WIN55,212-2 activated G␣ i/o , G␤␥, and G␣ q ; and cannabidiol activated G␣ s independent of CB 1 . Conclusion: Cannabinoids displayed functional selectivity. Significance: CB 1 functional selectivity may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
169
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(175 citation statements)
references
References 65 publications
5
169
1
Order By: Relevance
“…Thus, it appears that the recruitment of b-arr1 to CB 1 R-WT is very weak, so that it challenges the limits of detectability via the (otherwise quite sensitive) BRET approach applied here. However, our results showing a significant increase in b-arr1 BRET upon 2-AG stimulus are in accordance with recent results showing higher b-arr1 recruitment by 2-AG compared with WIN55 (Laprairie et al 2014). Taken together, recruitment of b-arr1 to CB 1 R-WT is obviously lower than that of b-arr2, but both are substantially enhanced in the CB 1 R-AAY mutant.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Thus, it appears that the recruitment of b-arr1 to CB 1 R-WT is very weak, so that it challenges the limits of detectability via the (otherwise quite sensitive) BRET approach applied here. However, our results showing a significant increase in b-arr1 BRET upon 2-AG stimulus are in accordance with recent results showing higher b-arr1 recruitment by 2-AG compared with WIN55 (Laprairie et al 2014). Taken together, recruitment of b-arr1 to CB 1 R-WT is obviously lower than that of b-arr2, but both are substantially enhanced in the CB 1 R-AAY mutant.…”
Section: Discussionsupporting
confidence: 81%
“…The binding between b-arrs and CB 1 R is relatively weak, and the affinity of the receptor for b-arr2 (b-arr2) is substantially higher than that for b-arr1 (b-arr1) (Gyombolai et al 2013). Furthermore, b-arr1 recruitment of CB 1 R appears to be agonist-dependent (Laprairie et al 2014, Flores-Otero et al 2014. Interestingly, in addition to canonical G-protein-mediated intracellular effects, recent data have suggested that the existence of b-arr-mediated, G-protein-independent signaling of CB 1 R, i.e.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…There is precedence for both ligand-and cell-type-specific differences in CB 1 R signaling Laprairie et al 2014). Ligands for CB 1 R, including the ECBs, synthetic cannabinoids such as WIN and phytocannabinoids such as Δ 9 -tetrahydrocannabinol, all bind different residues on the receptor.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, eCB, synthetic cannabinoids and phytocannabinoids exhibited biased signaling at CB 1, and activation of CB 1 by Gαi/o-and Gβγ-selective ligands might be therapeutically beneficial in HD [64][65][66]. Indeed, in vitro treatment of striatal cell model of HD with AEA normalized CB 1 protein levels and this effect was associated with improved cell viability, ATP production, BDNF-2 expression and inhibition of GABA release [64][65][66].…”
Section: The Link Between Hd and Cb 1 Receptor-mediated Protective Acmentioning
confidence: 99%